Status Konservasi dan Pelestarian Habitat Kucing Merah (Catopuma badia) di Hutan Kalimantan - Azzahra, Tiara Alifia; Dwinta Buntar, Asri; Pradipta Arya, Ghazi; Adistya Rahmaniar, Vira; Suryanda, Ade (Fakultas Biologi Universitas Gadjah Mada, 2024)
Indonesia is a country with vast animal diversity. In Kalimantan Island, there is an endemic animal that is rarely sighted and endangered, this animal is called Red Cat. Kalimantan Red Cat or Borneo Bay Cat (Catopuma badia) is a protected wild cat in Indonesia. The spread of these cats is also found in Northern Kalimantan which is in Sabah and Sarawak of Malaysia, it's also found in Indonesian forest. Red cats have dark chestnut red and faintly spotted fur, short rounded heads with orange-brown color. The ears of these cats are either black or dark brown colored, and its tail has a white line with dark spot at the tip of the tail. Until now, the population of these cats are unknown and categorized in an endangered conservation status by IUCN (International Union for Conservation of Nature) red list. Based on its status, the Kalimantan red cat is facing extinction risk in nature. Its status is endangered. The main problem is the lack of research information about its ecology and biology. These are very influential in conservation efforts.